When booming in the ears is more than benign tinnitus - Bryan Kharbanda; Nicholas San Roman (JEM Reports, 2025)
Background: Patients commonly present to the emergency department (ED) after initial outpatient evaluations fail to achieve timely diagnosis or symptom control. Many subjective-seeming neurologic symptoms affect a large portion of the US population at least once in a patient's lifetime (tinnitus 15 %, dizziness 30 %, and vertigo 40 %) but remain a diagnostic and treatment challenge for physicians. The ED in the United States plays a major role in risk stratifying these complex patients. Case presentation: A 49-year-old woman with history of hypertension presents to the ED complaining of hearing a “booming” sensation synchronous with her pulse in her right ear for weeks. She was initially evaluated by her primary care physician and diagnosed “possible tinnitus” and referred to ENT. There, she received an audiogram deemed “normal.” Weeks after her initial evaluation, she mentioned new and progressing symptoms of dizziness to her primary care physician who thus referred her to the ED. In the ED, the patient was found to be hypertensive, anxious, and with slight ataxia. CT angiography of the head and neck found complete occlusion of the left internal carotid throughout the entire left cervical region. The patient was started on heparin, anti-hypertensive medications, and transferred to a comprehensive stroke center after discussion with their neuro-interventionalist. Why should an emergency physician be aware of this?: Pulsatile tinnitus (PT) is rare but the causative differential diagnosis is vast and may be complex. PT should be considered an otologic symptom rather than its own diagnosis. Recent data suggests that an underlying cause can be identified in about 70 % of PT cases through proper diagnostic work-up (6). Failure to recognize the need for further work-up and diagnostics could lead to significant morbidity and mortality. Early recognition is crucial as treatment options are available to mitigate permanent neurologic deficits or death for dangerous causes. The treatment options vary markedly, however, depending on the ultimate etiology for PT. Accurate and timely diagnosis entirely drive effective management of pulsatile tinnitus.